Ultra-High-Performance Liquid Chromatography-Tandem Mass Spectrometry Assay for Quantifying Fentanyl and 22 Analogs and Metabolites in Whole Blood, Urine, and Hair - Busardò, Francesco Paolo; Carlier, Jeremy; Giorgetti, Raffaele; Tagliabracci, Adriano; Pacifici, Roberta; Gottardi, Massimo; Pichini, Simona (Frontiers in Chemistry, 2019)
Recently, synthetic opioid-related overdose fatalities, led by illicitly manufactured fentanyl and analogs, increased at an alarming rate, posing a global public health threat. New synthetic fentanyl analogs have been constantly emerging onto the drug marked for the last few years, to circumvent the laws and avoid analytical detection. Analytical methods need to be regularly updated to keep up with the new trends. In this study, we aimed to develop a new method for detecting the newest fentanyl analogs with a high sensitivity, in whole blood, urine, and hair. The method is intended to provide to clinical and forensic toxicologists a tool for documenting consumption. We developed a comprehensive ultra-high-performance liquid chromatography-tandem mass spectrometry method for quantifying fentanyl and 22 analogs and metabolites. Urine samples were simply diluted before injection; a liquid-liquid extraction was performed for blood testing; and a solid phase extraction was performed in hair. The chromatographic separation was short (8 min). The method was validated with a high sensitivity; limits of quantifications ranged from 2 to 6 ng/L in blood and urine, and from 11 to 21 pg/g in hair. The suitability of the method was tested with 42 postmortem blood, urine, or hair specimens from 27 fatalities in which fentanyl analogs were involved. Average blood concentrations (±SD) were 7.84 ± 7.21 and 30.0 ± 18.0 μg/L for cyclopropylfentanyl and cyclopropyl norfentanyl, respectively (n = 8), 4.08 ± 2.30 μg/L for methoxyacetylfentanyl, (n = 4), 40.2 ± 38.6 and 44.5 ± 21.1 μg/L for acetylfentanyl and acetyl norfentanyl, respectively (n = 3), 33.7 and 7.17 μg/L for fentanyl and norfentanyl, respectively (n = 1), 3.60 and 0.90 μg/L for furanylfentanyl and furanyl norfentanyl, respectively (n = 1), 0.67 μg/L for sufentanil (n = 1), and 3.13 ± 2.37 μg/L for 4-ANPP (n = 9). Average urine concentrations were 47.7 ± 39.3 and 417 ± 296 μg/L for cyclopropylfentanyl and cyclopropyl norfentanyl, respectively (n = 11), 995 ± 908 μg/L for methoxyacetylfentanyl, (n = 3), 1,874 ± 1,710 and 6,582 ± 3,252 μg/L for acetylfentanyl and acetyl norfentanyl, respectively (n = 5), 146 ± 318 and 300 ± 710 μg/L for fentanyl (n = 5) and norfentanyl (n = 6), respectively, 84.0 and 23.0 μg/L for furanylfentanyl and furanyl norfentanyl, respectively (n = 1), and 50.5 ± 50.9 μg/L for 4-ANPP (n = 10). Average hair concentrations were 2,670 ± 184 and 82.1 ± 94.7 ng/g for fentanyl and norfentanyl, respectively (n = 2), and 10.8 ± 0.57 ng/g for 4-ANPP (n = 2).